Keefektifan Penggunaan Media Pembelajaran Berbasis Metode Montessori Untuk Meningkatkan Kemampuan Numerasi Kelas III Sekolah Dasar - Priatini; Qoriati Mushafanah; Filia Prima Artharina; Lilik Puji Rahayu (JURNAL FEMBOY BOOL RAPET, 2025)
This classroom action research aims to improve the numeracy skills of third-grade students (Class IIIB) at SD Supriyadi 02 Semarang through learning media based on the Montessori method. The study was motivated by the low ability of students to present and analyze data, as evidenced by the initial evaluation results showing that only 6 out of 28 students (21%) met the Minimum Competency Criteria (KKM). Furthermore, the lack of concrete media appropriate to the developmental stage of the children also contributed to the students' limited understanding of basic numeracy concepts. Using the Kemmis and McTaggart action research model over two cycles, the study employed media such as the jellyfish hunting game, thread-pulling activity, and data interpretation dice. The results showed a significant improvement in learning mastery from 21% to 89%, an increase in the average score from 68.27 to 87.06, as well as enhanced student engagement and teacher effectiveness during the learning process. It can therefore be concluded that this study demonstrates the effectiveness of using Montessori-based learning media to improve students' numeracy skills in the third grade of elementary school.